The Importance of Breakfast - Claudia Peñuela (EDIS, 2009)
FCS1059b, a 2-page fact sheet by Claudia Peñuela, describes the benefits of this most important meal of the day, gives some reasons why people skip breakfast, and provides healthy recommendations and ideas. Includes references. Published by the UF Department of Family Youth and Community Sciences, August 2009.